if any number has a power 0
then the number directly becomes 1
2^0 = 1
7^0 = 1
x^0 = 1
therefore
x/[(2x^0)^0]
x/[1^0]
x/1 = x
simple...!!!
2007-02-01 19:05:06
·
answer #1
·
answered by nUssie.. 2
·
1⤊
1⤋
I may be totally wrong. But 10^2=100, 10^1=10, 10^0=1
Following the above which is easy to prove, your problem seems to say first, (2 * X^0) that would become 2 * 1 according to the above line. Next you have what became (2)^0 which also equals 1. ( all of this supposes that X > 0, if X = 0 then the equation would crash and burn)
For that reason, if your problem is correctly stated, the result of your equation is: X/1 =X.
For the proof that 10^0 = 1 you only need to know that 10^1= 10 and that 10^(-1)= 1/(10^1) then you may say 10/10 = 10^(1 -1) = 10^0 = 1
If I am wrong let me know. If you mis-stated the problem, try again.
2007-02-02 09:19:35
·
answer #2
·
answered by Fuzzy 7
·
0⤊
1⤋
2x^0 is 2, but 2^0 = 1, so the answer is x.
2007-02-02 03:06:36
·
answer #3
·
answered by gp4rts 7
·
0⤊
0⤋
x/ [(2x^0)^0]
x/ [1]
x
anything to the 0th power is always 1 (ex. x^0 = 1 , 5^0 = 1)
2007-02-02 03:25:56
·
answer #4
·
answered by Pure 2
·
0⤊
0⤋
No. x/((2x^0)^0)=x/(2*1)^0=x/1=x
for any a not equal to zero
a^0=1
2007-02-02 04:19:42
·
answer #5
·
answered by yupchagee 7
·
0⤊
0⤋
Hi Kai - you R a student of biology.
In this question, you seemed excited by the (x^0)^0
Everyone told You that it is = 1
No one above have shown you why x^0 = 1
Let me show:
x^0 = {x}^(1-1) = (x^1) * (x^-1)
= (x) * (1/ x) = x / x = 1
Anything to the power zero is ONE.
rest is simple.
2007-02-02 03:37:15
·
answer #6
·
answered by anil bakshi 7
·
0⤊
0⤋
x/[(2x^0)^0] = x/[(2*1)^0] = x/[2^0] = x/1 = x
2007-02-02 03:05:18
·
answer #7
·
answered by Northstar 7
·
0⤊
0⤋
x/[(2x^0)^0]=
=x/[(2*1)^0]=
=x/(2^0)=
=x/1=
=x
here, x:R, x^0 is always 1.
2007-02-02 03:15:04
·
answer #8
·
answered by happyrabbit 2
·
0⤊
0⤋
answer is x
recall that anything raised to the power of zero is equal to one
x/[(2x^0)^0]
x/[(2*1)^0]
x/[(2)^0]
x/[1]
x
2007-02-02 03:06:34
·
answer #9
·
answered by creditcardrabbit 2
·
0⤊
0⤋
x/[(2x^0)^0]
= x/[(2*1)^0]
=x/(2^0)
=x/1
=x
since any no. raised to power 0 is 1
2007-02-02 03:18:46
·
answer #10
·
answered by iron muncher 3
·
0⤊
0⤋